2019
DOI: 10.1371/journal.pone.0220825
|View full text |Cite
|
Sign up to set email alerts
|

Coagulant activity of recombinant human factor VII produced by lentiviral human F7 gene transfer in immortalized hepatocyte-like cell line

Abstract: Human mesenchymal stem cells (hMSCs) have the potential to differentiate into hepatocyte-like cells, indicating that these cells may be the new target cell of interest to produce biopharmaceuticals. Our group recently established a hMSC-derived immortalized hepatocyte-like cell line (imHC) that demonstrates several liver-specific phenotypes. However, the ability of imHC to produce coagulation factors has not been characterized. Here, we examined the potential for imHC as a source of coagulation protein product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(35 reference statements)
0
2
0
1
Order By: Relevance
“…FVII wild type (WT) was constructed as described previously [ 48 ]. Human FVII WT complementary DNA (cDNA) was ligated into the pTG19-T polymerase chain reaction cloning vector (Vivantis Technologies), which was used as a template for mutant FVII D60A cloning.…”
Section: Methodsmentioning
confidence: 99%
“…FVII wild type (WT) was constructed as described previously [ 48 ]. Human FVII WT complementary DNA (cDNA) was ligated into the pTG19-T polymerase chain reaction cloning vector (Vivantis Technologies), which was used as a template for mutant FVII D60A cloning.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, unlike most other organs, the introduction of exogenous hepatocytes into the liver parenchyma is a relatively simple undertaking, suggesting that the liver is highly amenable to tissue therapy using induced pluripotent stem cell-derived hepatocytes (8,9). Several studies showed that human mesenchymal stem cells (MSCs) derived from adipose tissue, bone marrow, or umbilical cord blood are capable of differentiating into hepatocyte-like cells (HLCs) in specialized in vitro culture conditions (10)(11)(12)(13)(14). Recent studies also demonstrated that hepatocytes derived from human adipose stem cells (hADSCs) are a potentially scalable and applicable alternative to human hepatocytes (13,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, unlike most other organs, the introduction of exogenous hepatocytes into the liver parenchyma is a relatively simple undertaking, suggesting that the liver is highly amenable to tissue therapy using induced pluripotent stem cell-derived hepatocytes 8,9 . Several studies showed that human mesenchymal stem cells (MSCs) derived from adipose tissue, bone marrow, or umbilical cord blood are capable of differentiating into hepatocyte-like cells (HLCs) in specialized in vitro culture conditions [10][11][12][13][14] . Recent studies also demonstrated that hepatocytes derived from human adipose stem cells (hADSCs) are a potentially scalable and applicable alternative to human hepatocytes 13,15−18 .…”
Section: Introductionmentioning
confidence: 99%